2007
DOI: 10.1088/0264-9381/24/20/008
|View full text |Cite
|
Sign up to set email alerts
|

Tidal dynamics in cosmological spacetimes

Abstract: We study the relative motion of nearby free test particles in cosmological spacetimes, such as the FLRW and LTB models. In particular, the influence of spatial inhomogeneities on local tidal accelerations is investigated by means of simple spherically symmetric models. The implications of our results for the dynamics of the solar system are briefly discussed. That is, on the basis of the models studied in this paper, we estimate the tidal influence of the cosmic gravitational field on the orbit of the Earth ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…Bonnor [11] concluded that the local systems expand but at a rate which is negligible compared with the general cosmic expansion. Similar conclusion was reached by Mashhoon et al [77] who analysed the tidal dynamics of test particles in the Fermi coordinates.The vacuole solutions are not appropriate for adequate physical solution of the N-body problem in the expanding universe. There are several reasons for it.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Bonnor [11] concluded that the local systems expand but at a rate which is negligible compared with the general cosmic expansion. Similar conclusion was reached by Mashhoon et al [77] who analysed the tidal dynamics of test particles in the Fermi coordinates.The vacuole solutions are not appropriate for adequate physical solution of the N-body problem in the expanding universe. There are several reasons for it.…”
supporting
confidence: 83%
“…Current paradigm is that the cosmological generalization of the Newtonian field equations of an isolated gravitating system like the solar system or a galaxy or a cluster of galaxies can be easily obtained by just making use of the linear principle of superposition with a simple algebraic addition of the local system to the tensor of energy momentum of the background matter. It is assumed that the superposition procedure is equivalent to operating with the Newtonian equations of motion derived in asymptotically-flat spacetime and adding to them ("by hands") the tidal force due to the presence of the external universe (see, for example, [77]). Though such a procedure may look pretty obvious it lacks a rigorous mathematical analysis of the perturbations induced on the background cosmological manifold by the local system.…”
Section: Brief History Of Cosmological Perturbation Theorymentioning
confidence: 99%
“…As in the case of the PA and, to a lesser extent so far, the FA, also such an alleged anomaly motivated many researches to find viable explanations in terms of various either conventional or unconventional physical mechanisms. 159,206,[282][283][284][285][286][287][288][289][290][291][292][293][294][295][296] The various attempts 154,[279][280][281] to investigate it have been performed so far within the framework of the International Astronomical Union (IAU) 1976 System of Astronomical Constants, available on the Internet at http://www.iau.org/static/resolutions/ IAU1976_French.pdf, which, in turn, is reminiscent of pre-relativistic eras when, among other things, only relative distances (expressed in astronomical units) in the Solar system could be determined since absolute ones could not be estimated with high accuracy. More precisely, the IAU 1976 system prescribed to measure the masses in units of Solar masses, the durations in days D (made of 86400 seconds), and the distances in astronomical units of length.…”
Section: The Anomalous Secular Increase Of the Astronomical Unitmentioning
confidence: 99%
“…The metric (20) describes a spherically symmetric and dynamical black hole in a FRW background more general than de Sitter. In this case, the event horizon may not be well-defined, but the AH always exists.…”
Section: Evolution Of the Apparent Horizonsmentioning
confidence: 99%